Actinic Cheilitis: Report of Three Cases and Review of Literature - Boza Oreamuno DDS, MSc, Yadira V.; Guillén Colombari DDS, MSc, Path, Diego (Odovtos - International Journal of Dental Sciences, 2018)
Actinic cheilitis (AC) is a potentially malignant lip disorder induced by chronic exposure to ultraviolet light, which mainly affects the vermilion of the lower lip of adults and fair skin. If it is not treated in a timely manner it can become a squamous cell carcinoma of the lip. Histologically, AC presents a series of alterations at the epithelial level ranging from hyperplasia to dysplasia; Connective tissue presents different degrees of actinic elastosis accompanied by inflammatory infiltrate. The objective of this work is to present three cases of patients with AC and analyze their clinical and histopathological characteristics.